THE EFFECT OF INTELLECTUAL CAPITAL ON COMPANY DEVELOPMENT AND FINANCIAL PERFORMANCE IN COMPANIES LISTED IN JAKARTA ISLAMIC INDEX FOR 2014-2018 PERIOD - Rachman Sugiharno; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2020)
The research aims to find out how to determine investors' decisions in transacting Islamic shares in the capital market. The method used is a qualitative approach with a descriptive case study method. The informant determining technique uses snowball and purposive sampling. data collection techniques using direct interviews, documentation and observation. After collecting data, the results of the study were analyzed using triangulation analysis to arrive at conclusions. The results of this study show that investors in transacting Islamic shares are divided into three parts, namely: from the type of investor, from the purpose of choosing Islamic shares and looking at the macro or micro side.Keywords: investor preferences, sharia stock, type of investors, macro side, micro sideREFFERENCE Bungin, B. (2011). Penelitian kualitatif. Jakarta: Kencana.Bursa Efek Indonesia. (2010). Panduanindeks harga saham bursa efek Indonesia. Jakarta: Bursa Efek Indonesia.Departemen Agama Republik Indonesia. (2012). Al-Quran dan terjemahannya. Jakarta: Departemen Agama Republik IndonesiaFardiansyah. (2002). Kiat dan strategi menjadi investor piawai. Jakarta: PT. Elex Media Komputindo.Ghozali, Imam. (2011). Aplikasi analisis multivariate dengan program IBM SPSS 19, edisi kelima. Semarang: Universitas DiponegoroHuda, N., & Mustafa Edwin Nasution. (2007). Investasi pada pasar modal syariah. Jakarta: Kencana.Husnan, S. (2003). Dasar-dasar teori portofolio dan analisis sekuritas. Yogyakarta: UPP STIM YKPN.Jogiyanto. (2010). Teori portofolio dan analisis investasi. Yogyakarta: BPFE.Kertonegoro, S. (2000). Analisa dan manajemen investasi. Jakarta: PT. Widya Press.Majelis Ulama Indonesia. (2003). Himpunan fatwa-fatwa Dewan Syariah nasional. Jakarta: DSN MUI bekerjasama dengan Bank Indonesia.Melicher, R., & Edgar A., N. (2003). Finance: Introduction to institutions, investment, and management. USA: John Wiley & Sons, Inc.Ryandono, M. Nafik Hadi. (2009). Bursa efek dan investasi syariah. Jakarta: PT Serambi Ilmu Semesta.Oyedele, J. B., McGreal, S., Adair, A., & Ogedengbe, P. (2013). Performance and role of European listed infrastructure in a mixed-asset portfolio. Journal of Financing Management of Property and Construction, 18(2), 160-183.Sugiyono. (2014). Metode penelitian kuantitatif, kualitatif, R&D, edisi 20. Bandung: Alfabeta.Sujawerni, Wiratna. (2014). SPSS untuk penelitian. Yogyakarta: Pustaka Baru Press.Susanti, & Syahyunan. (2012). Analisis pembentukan portofolio optimal saham dengan menggunakan model indeks tunggal (studi pada saham LQ-45 di Bursa Efek Indonesia periode Agustus 2009-Juli 2012). Media Informasi Manajemen, 1(4), 1-13.Tandelilin, E. (2010). Portofolio dan investasi. Yogyakarta: Kanisius.